Using AHP Method for Making a Decision on How the Management of Sewage Sludge in the Northern Croatia - Dušak, Vesna; Gotal Dmitrović, Lovorka; Bagnall, Renata (Journal of Information and Organizational Sciences, 2017)
By 2018, in Croatia, the agglomerations for collecting the sewage and water treatment systems are going to be constructed. All devices will be based on the mechanical-biological method of purification. However, the work of water treatment system produces a problem of sludge management. The paper presents the challenges of wastewater sludge handling and makes a decision on further sludge management. The hierarchical model of the decision making problem by defining the goal, criteria and alternative solutions is developed. On each level of the hierarchical model the elements of the model are compared with each other in pairs, and the preferences are expressed by using the Saaty’s scale. Moreover, the APH model compares the alternative pairs (thermal processing, deposition on agricultural land, disposal to waste repositories and composting) among each others. The intensities and weight preferences of one alternative over another are selected within the required criteria (economic, environmental, organisational and sociological).